Lendo Zora Hurston: a obra Mules and Men e sua relação com a teoria e a história da antropologia - Bemerguy, Telma (Cadernos de Campo (São Paulo, 1991), 2021)
In this essay, seeking to highlight the exclusionary processes that shape the irreproachable fixity of the anthropological canons, I propose an alternative to the white and male reading framework that usually characterizes the first years of contact with anthropological theory at the university in Brazil. I present a reading on “Mules and Man”, a book by Zora Hurston, an African American intellectual and a little recognized student of Franz Boas, “father” of the Cultural Anthropology. Starting from the dispute on the classification of the book over time, I seek to indicate how the author dialogued with the anthropological theories of the period, recovering events and debates that will allow us to see how Zora Hurston's work ended up being little recognized by anthropologists of the time, resulting in a long period of invisibility of her contributions to the discipline.